Mindfulness based on Cognitive therapy - M. Shojaeyan; Kh. Abolmaali (Afarand Scholarly Publishing Institute, 2016)
Aims: Some of the present psychotherapy help challengaes in the veterans are reductions in the level of mental health and psychological capital of the veterans caused by the war damages, which require more attentions. The aim of the study was to determine the effects of mindfulness, based on the cognitive therapy, on the increasement of the psychological capital dimensions, including resilience, self-efficacy, optimism, and hope, in the veterans.   Materials & Methods: In the controlled pretest-posttest quasi-experimental study, 20 veterans referred to Tehran Khatam-al-Anbia Hospital were studied in 2015. The injury percentage of the veterans was 70%, and they had a weak psychological capital. The subjects, selected by purposeful sampling method, were randomly divided into two groups including experimental and control groups (n=10 persons per group). Eight 120-minute cognitive therapy intervention sessions, based on mindfulness, was conducted in experimental group. Data was collected using Luthans psychological capital scale both in the pretest and posttest stages. Data was analyzed using multivariate covariance analysis with adjusted pretest effect. Findings: Mean posttest scores of self-efficacy, optimism, hope, and resilience in experimental group were more than control group (p<0.01). In addition, the treatment mindfulness intervention based on the cognitive therapy could explain 61.3, 78.6, 56.6, and 66.7% of self-efficacy, optimism, hope, and resilience variances, respectively. Conclusion: Mindfulness based on the cognitive therapy can increase the dimensions of the psychological capital including resilience, self-efficacy, hope, and optimism in the veterans.